Pandangan Guru Terhadap Pelaksanaan Kurikulum 2013 Muatan Lokal Bahasa Jawa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
This research on teachers' views on the implementation of the curriculum aims to find out the views of teachers regarding the implementation of the 2013 curriculum local content of the Javanese Language in Central Java Province, Indonesia. The teacher's view is important as a basis for implementing the 2013 curriculum. Based on the results of the preliminary study, it is known that in the field implementation, the 2013 curriculum for local content of the Javanese language is still not suitable for both elementary and high school levels. Research data was taken by questionnaires and FGDs conducted by researchers. The results of research activities show that 1) teachers' views on the material in the curriculum. This understanding includes the teacher's understanding of the material and the development of the material in the curriculum as well as students' understanding of the learning material from the teacher's point of view, and 2) the teacher's view of the suitability of the material in the curriculum with students. The Javanese language local content teachers hope that there is an improvement in the 2013 Javanese language local content curriculum based on the results of the curriculum review carried out so that the implementation is better and more optimal.